2021
DOI: 10.15700/saje.v41n2a1894
|View full text |Cite
|
Sign up to set email alerts
|

The predictive influence of gender, onset of deafness and academic self-efficacy on the attitudes of deaf learners towards Biology

Abstract: In the study reported on here we examined the attitudes of deaf learners towards biology in Ibadan, Nigeria. Forty-one deaf learners (28 males; 13 females) in the Secondary School II science classes from 3 government-funded secondary schools for the deaf were purposively selected for the study. In the study we adopted a descriptive survey research design of the correlational type. Four research questions were raised and answered. A structured questionnaire, “Deaf Learners and Biology Questionnaire” with a reli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…This implies that, irrespective of onset of deafness (prelingual or postlingual) motivation of the participants to have better mathematics performance is influenced by the variants of the treatment plan. Adigun and Nzima (2021) and Ogundiran and Olaosun (2013) note that language proficiency is an important factor that may inform achievement motivation. However, this study observed that language ability may not be comprehensively responsible for achievement motivation but for the active and positive learning environment and or instructional design that speaks directly to the emotion and cognition of deaf learners.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This implies that, irrespective of onset of deafness (prelingual or postlingual) motivation of the participants to have better mathematics performance is influenced by the variants of the treatment plan. Adigun and Nzima (2021) and Ogundiran and Olaosun (2013) note that language proficiency is an important factor that may inform achievement motivation. However, this study observed that language ability may not be comprehensively responsible for achievement motivation but for the active and positive learning environment and or instructional design that speaks directly to the emotion and cognition of deaf learners.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence in the last two decades have shown that deaf learners are between 2 and 4 years lagging behind their hearing peer in language acquisition and skills (Barbosa, 2013; Henner et al, 2021; Swanwick et al, 2005; Traxler, 2000; Tuller & Delage, 2014). Although, language potential of the deaf learner and their non‐deaf peer differs significantly when compared but even among the deaf learners, language abilities and richness in vocabulary content varies between those who are prelingually deaf and postlingually deaf (Adigun & Nzima, 2021; Ogundiran & Olaosun, 2013).…”
Section: Background To the Studymentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, due to their hearing conditions and the associated psychological and social challenges Pizzo, 2016), LDHH experience uneven academic treatment, with a reduced expectation of their strength for science engagement and unequivocal science achievement . Some studies have expressed the dissatisfaction of stakeholders (for example, parents, teachers, and education officers) regarding the under-representation of LDHH in the sciences, as well as the abysmal performance of LDHH in science subjects (Adigun & Nzima, 2021;Ogundiran & Olaosun, 2013). Regardless of past reports on science engagement by LDHH, the current global situation, due to COVID-19, might have further stimulated the interest of many LDHH to undertake science instruction.…”
Section: The Literature Reviewmentioning
confidence: 99%